INVESTMENT AND EXPORT EFFECT ON POVERTY THROUGH GROWTH: EVIDENCE FROM INDONESIA’S NICKEL PRODUCING PROVINCES - Muhammad Yusrun Najah (Journal of Applied Economics in Developing Countries, 2025)
This study investigates the effect of investment and exports on poverty, considering the role of economic growth as a mediating variable. It uses a quantitative approach through path analysis and panel data from 2013 to 2024 in four nickel-producing provinces, namely North Maluku, Southeast Sulawesi, South Sulawesi, and Central Sulawesi. The results show that investment and exports contribute directly to economic growth, but only investment has a significant impact on poverty reduction. Indirectly, neither has a significant effect on poverty through economic growth. These findings indicate that the growth that has occurred is not yet inclusive, so it is necessary to strengthen access to basic services and create jobs in labor-intensive sectors to encourage a more equitable distribution of economic benefits.